Structural Ambiguity Interpretation: A Case Study of Arab Learners of English (Global Journal of Human-Social Science, 2012)
The aim of this paper is to investigate how Arabic native speakers non-native speakers of English interpret English ambiguous sentences It has been recognized that Arabic native speakers encounter problems with English sentences which involve structural ambiguity Sixty subjects participated in the experiment All were university students specialized in English The subjects were given ambiguous sentences contain prepositional phrases relative clauses etc For instance prepositional phrases like the girl hit the boy with the book in which the prepositional phrase PP can be attached either to the verb phrase VP or to the preceding noun phrase NP It has been recognized that the students face difficulty in interpreting ambiguous structure and generally take the general meaning which can be understood from the sequence of words
Keywords: Ambiguity; Arabic; translation; structural ambiguity; lexical ambiguity